ERS technical standard on bronchial challenge testing: pathophysiology and methodology of indirect airway challenge testing - Hallstrand, T.; Leuppi, J.; Joos, G.; Hall, Graham; Carlsen, K.; Kaminsky, D.; Coates, A.; Cockcroft, D.; Culver, B.; Diamant, Z.; Gauvreau, G.; Horvath, I.; et al. (2018)
Copyright ©ERS 2018. Recently, this international task force reported the general considerations for bronchial challenge testing and the performance of the methacholine challenge test, a "direct" airway challenge test. Here, the task force provides an updated description of the pathophysiology and the methods to conduct indirect challenge tests. Because indirect challenge tests trigger airway narrowing through the activation of endogenous pathways that are involved in asthma, indirect challenge tests tend to be specific for asthma and reveal much about the biology of asthma, but may be less sensitive than direct tests for the detection of airway hyperresponsiveness. We provide recommendations for the conduct and interpretation of hyperpnoea challenge tests such as dry air exercise challenge and eucapnic voluntary hyperpnoea that provide a single strong stimulus for airway narrowing. This technical standard expands the recommendations to additional indirect tests such as hypertonic saline, mannitol and adenosine challenge that are incremental tests, but still retain characteristics of other indirect challenges. Assessment of airway hyperresponsiveness, with direct and indirect tests, are valuable tools to understand and to monitor airway function and to characterise the underlying asthma phenotype to guide therapy. The tests should be interpreted within the context of the clinical features of asthma.